TEACHING LISTENING OR TESTING LISTENING? - Kiren Kaur (TLEMC (Teaching and Learning English in Multicultural Contexts), 2017)
Listening is an important skill for communication and for learning yet it is a literacy area that is least taught in the Singapore classrooms. In order to prepare young learners for the demands of learning and communication, ways to teach listening, and not just test it, should be found. This paper focuses on a small scale study from an elementary school in Singapore where learners reported on their strategy use in diaries after listening to various types of English texts. The paper will report on strategy use by examining young learners’ responses. The paper will then discuss implications in terms of teaching listening to young learners of different proficiencies and explore how we can help prepare them for the demands of the real world in which a mastery of English and effective communication skills are perceived to be important assets.